Efficient Removal of Magnetic Contamination from Drilling Fluids – The Effect on Directional Drilling - Saasen, Arild; Poedjono, Benny; Ånesbug, Geir Olav; Zachman, Nicholas (Journal of Energy Resources Technology, 2021)
Magnetic debris in a drilling fluid have a significant influence on the ability of the drilling fluid to maintain its function. Down hole logging can suffer from poor signal to noise ratios. Directional drilling in areas close to the magnetic North Pole, such as in the Barents Sea, Northern Canada, or Russia, can suffer because of magnetic contamination in the drilling fluid. Magnetic particles in the drilling fluid introduce additional errors to the magnetic surveying compared to those normally included in the ellipsoid of uncertainty calculation. On many offshore drilling rigs, there are mounted ditch magnets to remove metallic swarf from the drilling fluid. These magnets normally only remove the coarser swarf. In this project, we use a combination of strong magnets and flow directors to significantly improve the performance of the ditch magnets. This combination, together with proper routines for cleaning the ditch magnets, significantly helps to clean the drilling fluid. Through the combined use of flow directors and ditch magnets, it was possible to extract more than five times as much magnetic contamination from the drilling fluid as normal compared with other proper ditch magnet systems. This is verified by comparing the ditch magnet efficiencies from two drilling rigs drilling extended reach drilling (ERD) wells in the North Sea area. In this paper, it is discussed how the accuracy of directional drilling and well position effected by various interferences can be improved by the use of a drilling fluid with minimal effect to the measurement while drilling (MWD) measurement. publishedVersion